Oxytetracycline marking studies of tilapia; Oreochromis niloticus. - Abdel-Hadi, Yasser Mohammed; Craig, J. F.; Babaluk, J. A.; Wassle, R. (2011)

(untitled)
Oxytetracycline (OTC) was intraperitoneally injected into tilapia, Oreochromis niloticus to validate aging of this fish, to determine suitable marking dosages of OTC, to assess OTC induced mortality and to determine the rate of OTC incorporation into 4 bony structures including scales, opercula, otoliths and pelvic fin rays' sections. The OTC was used in 3 doses; 12.5, 25 and 50 mgjkg of fish body weight. A total of 1200 fish with an average body weight of 60 grams were used for the experiment (300 fish per OTC dose and another 300 fish were injected with sterile saline solution as a control group). The fish of the 4 groups were released in the water of 4 raceways at the World Fish Centre, Abbassa, Egypt and were kept for an entire year. The results revealed that 1 annulus was laid down after the OTC mark on all bony structures. OTC was incorporated into all examined bony structures. The clearest OTC marks with minimal mortality were induced by the 25 mg OTC dosage. No significant mortalities were noticed among the injected fish with OTC.